2015
DOI: 10.1260/1747-9541.10.4.623
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Use of a Movement Assessment Protocol for Under-14 Rugby League Players in a Talent Development Environment

Abstract: This study investigated the use of a movement assessment protocol for under-14 rugby league players by evaluating the relationships between There is a need to educate coaches about the use of both fitness testing and qualitative movement assessments to identify talented U14 rugby league players, which potentially reduces relative age and maturational biases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Of these, 23 demonstrated advantages in these characteristics for athletes born closer to the beginning of the category year. However, it was found that relatively younger athletes with an early biological maturation have a disadvantage in anthropometric measurement and can match or have disadvantages in relation to performance in physical tests (Bliss & Brickley, 2011;Gutiérrez Díaz del Campo, et al, 2010;Votteler & Höner, 2014;Morley, et al, 2015;Figueiredo, et al, 2019). The researchers found that the observed differences regarding anthropometric data, physical performance, and maturation occur predominantly between the ages of 11 and 16, more precisely the pubertal commonly practiced in most countries, grouping athletes not only by chronological age, but also by weight, height, and mobility between competitive levels.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 23 demonstrated advantages in these characteristics for athletes born closer to the beginning of the category year. However, it was found that relatively younger athletes with an early biological maturation have a disadvantage in anthropometric measurement and can match or have disadvantages in relation to performance in physical tests (Bliss & Brickley, 2011;Gutiérrez Díaz del Campo, et al, 2010;Votteler & Höner, 2014;Morley, et al, 2015;Figueiredo, et al, 2019). The researchers found that the observed differences regarding anthropometric data, physical performance, and maturation occur predominantly between the ages of 11 and 16, more precisely the pubertal commonly practiced in most countries, grouping athletes not only by chronological age, but also by weight, height, and mobility between competitive levels.…”
Section: Resultsmentioning
confidence: 99%